POLITICAL EDUCATION TO INCREASE THE PARTICIPATION OF CONSTITUTIONAL LAW STUDENTS IN THE ELECTION OF DEWAN EKSEKUTIF MAHASISWA OF IAIN MADURA - Jihan Amalia Syahidah; Moh Zuhdi (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2022)
The declining attention of young voters on several aspects makes political education very vital for the sustainability of democracy in Indonesia. Political education for students who are young voters in this case are students of the Constitutional Law is considered important to increase their participation at the tertiary level, namely the election of DEMA (Student Executive Council) IAIN Madura. This study used an approach to students of the Constitutional Law study program, Islamic State Faculty of IAIN Madura through observation and interviews as well as data collection supported by document studies through several relevant kinds of literature so that data triangulation was then carried out to produce valid data. The results showed that in the aspect of students' initial knowledge about elections from several informants of the Constitutional Law study program students obtained data that they already had a good understanding of. Then on the aspect of student perspectives on campus politics, some of them do not know information about the election of the chairman of the DEMA (Student Executive Council) due to several reasons behind it. So then to increase student political participation in the election of the chairman of DEMA the author formulated three political stimuli, namely through learning political science courses, through campus organizations, and mass media.